Generation Y Investment Decisions in Medan City: Impact of Financial Literacy, Risk Perception, and Financial Behavior : Keputusan Investasi Generasi Y di Kota Medan: Dampak Literasi Keuangan, Persepsi Risiko, dan Perilaku Keuangan - Sri Puji Lestari; Muhammad Ridwan; Sri Fitri Wahyuni (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2025)
This study explores both the direct and indirect effects of financial literacy, risk perception, and financial behavior on the investment decisions of Generation Y individuals living in Medan City. Utilizing a quantitative research methodology, data analysis was performed using the Statistical Package for the Social Sciences (SPSS), with a specific focus on path analysis to examine the relationships among latent variables. The target population consisted of individuals aged 30 to 42 years, classified as Generation Y, totaling 587,743 persons in Medan City. The determination of the sample size was carried out using Slovin's formula, yielding a total of 100 respondents for the study. Data were obtained through observation and the administration of structured questionnaires. The findings indicate that financial literacy, risk perception, and financial behavior each exert a statistically significant and positive individual influence on investment decisions. Moreover, when analyzed simultaneously, these variables collectively contribute meaningfully and positively to the investment decision-making process among Generation Y in the target region. This study provides novel insights into the financial behavior of Generation Y in an urban Indonesian setting, highlighting the importance of financial knowledge, perceived risk, and behavioral tendencies in shaping investment choices. Limitations related to sampling bias, self-reporting, and regional scope are acknowledged, and future studies are encouraged to expand the geographic coverage and apply mixed methods for deeper analysis.